2018
DOI: 10.1002/lpor.201800032
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Orientations of the Electric and Magnetic Dipoles Induced in Silicon Nanoparticles for Multicolor Display

Abstract: Artificial control of colors based on plasmonic and dielectric nanostructures is not only interesting for fundamental research, but also important for practical applications. Apart from spatial resolution, chromaticity, angular independence, and dynamical color-tuning have emerged as the most desirable functions for structural color. Here, it is shown theoretically that the orientations of the electric or magnetic dipoles induced in a silicon nanoparticle can be manipulated by using an evanescent wave excited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Recently, it has been demonstrated that femtosecond laser ablation can be employed to fabricate semiconductor nanoparticles, such as silicon (Si) NSs which exhibit distinct electric and magnetic resonances in the visible to near‐infrared spectral region . Based on Mie theory and the complex refractive index reported for liquid Ga, one can expect that the ED and electric quadrupole (EQ) resonances of a liquid Ga NS will be shifted from the ultraviolet to visible light and even near‐infrared spectral region with increasing diameter of the liquid Ga NS (see , Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that femtosecond laser ablation can be employed to fabricate semiconductor nanoparticles, such as silicon (Si) NSs which exhibit distinct electric and magnetic resonances in the visible to near‐infrared spectral region . Based on Mie theory and the complex refractive index reported for liquid Ga, one can expect that the ED and electric quadrupole (EQ) resonances of a liquid Ga NS will be shifted from the ultraviolet to visible light and even near‐infrared spectral region with increasing diameter of the liquid Ga NS (see , Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, we show that a nano-antenna array composed of regularly arranged nano-antennas can be employed to steer the propagation direction of light beams with large diameters when the diffractions of the array are intentionally designed to be coincide with the deflection angles of single nano-antennas. For practical applications, the all-silicon nano-antennas sitting on a quartz substrate can be experimentally fabricated by using the techniques of wafer bonding, electron-beam lithography and reactive ion etching [55]. Apart from the wavelength and polarization demultiplexers proposed in this work, such nano-antennas may find possible applications in single photon emitters.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, Mie resonances in dielectric nanoparticles with large refractive indices can be employed to release the Ohmic loss [6][7][8][9]. Although an improvement of Q factor can be achieved in such a wavelength scale nanoparticles, because of its dielectric nature, the realization of high Q factor resonance is still hindered by the radiation loss of corresponding electromagnetic multipole modes (i.e.…”
Section: Introductionmentioning
confidence: 99%